Identification and Characterization of PrTK 2 Bacterial Isolate Producing Extracelular Protease Enzym From Tempeh Rubber Seeds - Cico Jhon Karunia Simamora; Sukmawati Sukmawati (UNIVERSITAS NEGERI PADANG, 2020)
Protease is an enzyme that can hydrolyze proteins into simpler compounds such as small peptides and amino acids. The enzymes produced by microorganisms can be isolated by separating cells by centrifugation. This study aims to determine the biological characteristics of the PrTK 02 bacterial isolate and the characteristics of the crude extract of the protease enzyme produced by the PrTK 02 bacterial isolate. The study was conducted by inoculating 1 ose PrTK 02 bacteria on the Nutrient Broth (NB) media. Pre-culture was carried out at 37 °C for 48 hours with an agitation speed of 120 rpm. Protease enzyme extraction was carried out by centrifugation of bacterial growth media at a speed of 3000 rpm for 15 minutes at 4 °C. Supernatant as a sample was tested for protease activity and protein content. The results of this study were obtained from the protease enzyme from bacterial isolate PrTK 02 marked by a clear zone in the medium of high school and the highest activity at the time of production 24 hours with the specific activity of the enzyme 1.2154 unit / mg protein. Biochemical and microscopic identification shows that the isolate of PrTk 02 bacteria is a class of Bacillus sp. PrTk 01 which is a Gram-positive bacteria that is found in tempeh.